Implementasi Permainan Edukatif “Petualangan Iman” untuk Menumbuhkan Sikap Optimis dan Pantang Menyerah - Muhammad Zafrul Khikam; Suhartini; Yenny Kusumaningrum; Lia Sofyana; Felicia Najwa Zahra (Jurnal Pendidikan Guru Profesional, 2025)
This study aims to describe the implementation of the educational game “Petualangan Iman” as a learning medium for Islamic Education in the topics of Fathul Makkah and the Farewell Pilgrimage at SDN 3 Panusupan. The method used includes observation, interviews, and documentation involving 20 fifth-grade students. The findings indicate that the educational game successfully increased students’ active participation by up to 75% and supported the internalization of optimism and perseverance through simulations, metaphors, and collaborative activities. The classroom teacher validated the game’s effectiveness in helping students understand the content in an enjoyable and cooperative manner. Although distractions occurred due to school programs such as MBG, the game continued effectively and achieved cognitive, affective, and social learning objectives. Thus, the “Petualangan Iman” game proves to be an effective and innovative Islamic Education learning strategy focused on character development.